In light of the DSM-5 dimensional model of personality: Borderline personality disorder at the crossroads with the bipolar spectrum - Henriques-Calado, Joana (2021)
Background. State-of-the-art research highlights that borderline personality disorder (PD) and bipolar spectrum disorders have clinical characteristics in common, which imply uncertainty in differential diagnoses. Although there is a growing body of literature on the DSM-5 dimensional model of personality disorder, its discriminative features between these clinical samples are still understudied. In this study, we seek to identify the best set of predictors that differentiate between borderline PD and bipolar spectrum, based on pathological and normative personality traits and symptoms. Methods. A cross-sectional study of three clinical samples: 1) Borderline PD group of 63 participants; 2) Major depressive disorder group of 89 participants; 3) Bipolar disorder group of 65 participants. Self-reported assessment: Personality Inventory for DSM-5; Brief Symptom Inventory; FFM Inventory. A series of one-way ANOVAs and logistic regression analyses were computed. Results. The major set of data emerging as common discriminants of borderline PD across the bipolar spectrum are unusual beliefs & experiences, paranoid ideation, obsession-compulsion and extraversion. Depressivity (OR: 34.95) and impulsivity (OR: 22.35) pathological traits displayed the greatest predictive values in the differential diagnosis. Limitations. The small size of the samples; a lack of data from participants’ previous clinical history. Conclusions. Findings support the DSM-5 pathological traits as differentiating borderline PD through bipolar spectrum, and reinforcing the joint use of symptom-related pathological functioning and normal-range personality traits. Alongside the bipolar spectrum, borderline pathology sheds light upon a hypothetical overlap along the depressive and schizoaffective/schizophrenia spectra, representing a borderland space at a crossroads with the psychopathology of a meta-spectrum.